2014
DOI: 10.1021/ja506472u
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Viridicatumtoxin B and Analogues Thereof: Strategy Evolution, Structural Revision, and Biological Evaluation

Abstract: The details of the total synthesis of viridicatumtoxin B (1) are described. Initial synthetic strategies toward this intriguing tetracycline antibiotic resulted in the development of key alkylation and Lewis acid-mediated spirocyclization reactions to form the hindered EF spirojunction, as well as Michael–Dieckmann reactions to set the A and C rings. The use of an aromatic A-ring substrate, however, was found to be unsuitable for the introduction of the requisite hydroxyl groups at carbons 4a and 12a. Applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 126 publications
0
42
0
Order By: Relevance
“…For instance, M. robertsii harbors a PKS pathway resembling that leading to the production of viridicatumtoxin in Penicillium aethiopicum, a tetracycline-like antibiotic active against gram + bacteria (Chooi et al, 2010;Gibson et al, 2014;Nicolaou et al, 2014 Deletion of the mrpptA gene resulted in nearly avirulent M. robertsii strains that never produced mycosed cadavers. In comparison, lysine auxotrophy or loss of siderophores attenuated virulence but nearly all dead insects inoculated with the ΔmrsidA or ΔmraarA produced conidiating cadavers (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, M. robertsii harbors a PKS pathway resembling that leading to the production of viridicatumtoxin in Penicillium aethiopicum, a tetracycline-like antibiotic active against gram + bacteria (Chooi et al, 2010;Gibson et al, 2014;Nicolaou et al, 2014 Deletion of the mrpptA gene resulted in nearly avirulent M. robertsii strains that never produced mycosed cadavers. In comparison, lysine auxotrophy or loss of siderophores attenuated virulence but nearly all dead insects inoculated with the ΔmrsidA or ΔmraarA produced conidiating cadavers (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The next day, 10 mL of LB media was inoculated with a single colony from each plate and incubated at 37 °C while shaking. Using a previously described protocol from Nicolaou et al, 58 B. subtilis 168 and MRSA131 were exposed to increasing concentrations of the tested antibiotic (0.125–64.0 μ g/mL; prepared in the Nicolaou laboratories) in LB broth and incubated overnight at 37 °C. The lowest concentration at which the antibiotic appeared to be inhibiting growth was determined to be the MIC for the drug.…”
Section: Methodsmentioning
confidence: 99%
“…Recently K.C. Nicolaou et al (2014), Cuixiang Sun et al (2015) and Hrvoje Petkovi et al (2015) reported novel tetracycline derivatives with extensions on the C and D rings. 8 These compounds showed antibacterial activity against a wide range of clinically important bacterial isolates, including multidrug-resistant, Gram-negative pathogens.…”
Section: Introductionmentioning
confidence: 99%